Dostoevsky in Kazakhstan: History of Study, Results, Prospects - Kenzhekhan Slyamzhanovich Matyzhanov; Svetlana V. Ananyeva (RUDN Journal of Studies in Literature and Journalism, 2021)
The article is devoted to the analysis of the Semipalatinsk and Kuznetsk periods in the life and work of F.M. Dostoevsky. The purpose of the study is to reveal the Kazakh-Siberian periods in the fate of the Russian writer, their reflection in the letters and works of art by F.M. Dostoevsky. In the year of the 200th anniversary of the birth of the Russian writer, we cannot talk about the complete study of the indicated periods of the life of the prose writer, which, of course, to one degree or another, were reflected in his prose. This determines the degree of novelty of this article. Dostoevsky is dear to Kazakhstan. He not only served his exile, but also found a friend here, sincere and quivering - the historian, orientalist, ethnographer Ch. Valikhanov. The stories Uncle's Dream and The Village of Stepanchikovo and Its Inhabitant, the first chapters of Notes from the Dead House were written in Semipalatinsk. The story The village of Stepanchikovo and its inhabitants (1857-1859) has the author's clarification: From the notes of the unknown. Many works of fiction in world literature are the result of travel notes, diaries. Undoubtedly, the restoration of the history of the Kazakh-Siberian period of the life and work of F.M. Dostoevsky is of great value, because the greatest Russian writer experienced spiritual revival there, in Kazahstan. The works of F.M. Dostoevsky were included in the literature program of secondary schools in Kazakhstan, translated into Kazakh ( The Idiot, The Brothers Karamazov translated by N. Syzdykov). Dostoevsky scholars of Kazakhstan in the XXI century continue to study the writers works.